Adaptive mindset: An effective approach to leadership in cross-cultural contexts - LOTZER, Francis (Institutional Knowledge at Singapore Management University, 2020)
Understanding cultural signals by exploring the ‘hidden part of the iceberg’ and communicating the benefits of change to team members.